ИСПОЛЬЗОВАНИЕ МИКРОКОНТРОЛЛЕРОВ СЕМЕЙСТВА AVR В СОВРЕМЕННЫХ СРЕДСТВАХ АВТОМАТИЗАЦИИ И ПРОГРАММНО-АППАРАТНЫХ КОМПЛЕКСАХ - Колесников, В.А.; Намазбаев, Т.С.; Моисеенко, В.Ю. (Изд-во КарГУ., 2009)
Мақала AVR тектес микробақылағыштар негізінде əзірленген осы заманғы мамандандырыл- ған автоматика құралы мен бағдарламалы-аспаптық кешендерге арналған. Ол жабдықтың негізгі құрамдық жəне жұмыс істеу сұлбасы келтірілген. Жабдықты əзірлеудің негізгі кезең- дері сипатталып, AVR тектес микробақылағыштар негізінде мамандандырылған жабдық- тар мен аспаптарды құрастыру əдісі қалыптасқан. This article is devoted to development of modern specialized means of automatics and hardwaresoftware complexes on the basis of microcontrollers of group AVR. There is the description of microcontrollers in the article, and there are also specialized hardware means based on microcontrollers of group AVR. The cores structural and functions charts of the specialized equipment are resulted. The basic development cycles of the specialized equipment are described. The technique of construction of the modern specialized equipment and the equipment on the basis of microcontrollers of group AVR is developed.
Keywords: использование микроконтроллеров; AVR; современная средства автоматизации; программно-аппаратный комплекс